Antigen pro diagnostiku klístové encefalitidy technikou ELISA - Grubhoffer, L; Kŕivanec, K; Tomková, E; Kopecký, J (Ceskoslovenska epidemiologie, mikrobiologie, imunologie, 1991)
From the brains of suckling mice infected with the virus of tickborne encephalitis, strain Hypr, the authors concentrated by precipitation with polyethylene glycol - 6000 and purified by differential ultracentrifuging on a linear saccharose gradient the virion antigen KEV-II for assessment of specific human antibodies, using the indirect ELISA technique. The antigen was characterized as to haemagglutination activity, electrophoretic properties, immunoblotting with a monoclonal antibody against external layer gpE and enzyme immune analysis to assess the relative ratio of gpE in the diagnostic antigen. Using the technique of indirect ELISA with antigen KEV-II, the authors examined in 1988 and 1989 sera of 631 patients with a specificity of estimations of 99.4% (0.6% falsely positive results) and sensitivity expressed by the liminal serum dilution rate of 1:1000.
Keywords: antigeny virové; Encephalitis Viruses, Tick-Borne; Humans; klíšťová encefalitida; Antigens, Viral; Enzyme-Linked Immunosorbent Assay; viry klíšťové encefalitidy; Encephalitis, Tick-Borne; lidé; ELISA